Experience delivering an integrated service model to people with criminal justice system involvement and housing insecurity - Olivia Baker; Chevaughn Wellington; Carolina R. Price; DeShana Tracey; Lindsay Powell; Sara Loffredo; Silvia Moscariello; Jaimie P. Meyer (BMC, 2023)
Abstract Background People returning to communities from prison or jail face stressors related to securing housing, including discrimination, restrictions based on prior felony convictions, and limited economic and social resources. Existing housing programs can effectively reduce housing instability but often do not fully address the needs of people involved in the criminal justice system experiencing homelessness who often have co-occurring chronic medical issues, and psychiatric and substance use disorders. Methods Project CHANGE is an ongoing program to deliver person-centered, integrated care and services to individuals involved with the criminal justice system and experiencing homelessness. Applying a Screening, Brief Intervention, (Referral to) Treatment framework, a comprehensive needs assessment is followed by delivery of intensive housing and vocational case management; and psychiatric, substance use, and medical services in a single location by an interdisciplinary team. Participants are followed with study interviews for 12 months. The current analysis was designed to assess the baseline characteristics and needs of the sample population, and the intensity of contact required for integrated service delivery. Results Between November 2019 and September 2021, 86 participants were enrolled, of whom 64% had been released from prison/jail in the past 6 months; the remainder were on parole, probation, or intensive pretrial supervision. Participants were unstably housed (64%) or residing outdoors (26.7%) or in a shelter (24.4%). Most participants had high medical need and frequent healthcare engagement through outpatient and emergency department visits. Most participants were at-risk for clinical depression, and half were diagnosed with anxiety, dissociative, stress-related, somatoform, and other non-psychotic psychiatric disorders. Over 12-month follow-up, the interdisciplinary team made over 500 contact encounters, over half of which resulted in direct services provided, including obtaining vital documents for homelessness verification, housing applications, and employment coaching. Conclusion Navigation of services can be particularly challenging for individuals experiencing criminal justice involvement, homelessness, and co-occurring medical, psychiatric, and substance use issues, which can be addressed holistically in an integrated service model. Integrated service delivery was time-, resource-, and staffing-intensive, and challenged by the COVID-19 pandemic, requiring innovative solutions to sustain participant engagement.